Comparative evaluation of the efficacy of phythotherapeutics and chemical products against tick in the control of the Boophilus microplus (Canestrini, 1887) through engorged female bioassey - Silva, F. F.; Soares, M. C. S. C.; Alves, L. C.; Lima, M. M.; Silva, L. V. A.; Faustino, M. A. G.; Silva Junior, F. F. (Univ Federal Rural Pernambuco, 2008)
The aim of this research was to evaluate the efficacy of plant extracts and chemical products for the control of Boophilus microplus. Three commercial products for the control of Boophilus microplus were in vitro evaluated, chemical compounds of cypermethrin + DDVP and organophosphate as recomended by the manufacturer, and also four plant extracts, Azadirachta indica (1%), Cymbopogon densiflorus, Lippia alba and Ipomoea asarifolia at different concentrations. The results showed that the chemical compounds tested had efficacy lower than 95% against the Boophilus microplus samples in the experiment. The extracts of all plants have shown some biological activity in the mortality of ingurgitated females and inhibition of egg crash, however the extract of Azadirachta indica presented efficacy higher than 95% in all tested concentrations, being the best sample tested in this experiment.
Keywords: Boophilus microplus; control; bovine